FARM MANAGEMENT INFORMATION SYSTEMS: A CASE STUDY ON A GERMAN MULTIFUNCTIONAL FARM - Husemann, Christoph; Novković, Nebojša (Economics of Agriculture, 2014)
Accurate and easy to use Farm Management Information Systems (FMIS) are of fundamental importance for a successful operational farm management. However, still today many farmers do not use FMISs for various reasons, like lack of knowledge and the complexity of many available FMISs. In particular for small to medium-sized farms and for multifunctional farms appropriate FMISs hardly exist. This paper aims on the deduction of a concrete FMIS from a general FMIS. The concrete FMIS has to focus on the needs of medium-sized and multifunctional farms. This means that the farmer has to be empowered to allocate the scarce resources of the farm. Therefore, we picked a German farm from the state North Rhine Westphalia as a case-study to apply a system analysis. The case study farm helps to identify and to analyze relevant material and information flows, production processes, and their interconnections and synergies.